Reconstruction of a Holocene landslide-dammed lake in the Yalong basin, eastern Tibetan Plateau - Wang, Hao; Yang, Anna; Jiang, Shengfan; Liu, Nannan (Frontiers in Earth Science, 2023)
The failures of natural dams formed by landslides and glaciers in mountain areas have triggered the most destructive flood events on Earth. Outburst floods are effective agents in modifying landscapes, such as carving bedrock gorges and transporting surface masses. Reconstructing the ages and magnitudes of prehistoric landslide damming events allows us to capture the full range of frequencies and magnitudes of similar events and deepen our understanding of the interaction between large landslides and trunk rivers in tectonically active high-relief mountains. Previous studies have revealed many paleo-landslide-dammed lakes in the Yarlung Tsangpo River and its tributaries, the Jinsha River and the Min River. However, most studies associated with paleo-event reconstruction lack an estimation of the extent and volume of paleo-landslide-dammed lakes. The paleo-level of a landslide-dammed lake can be recorded in the variation in the sedimentary sequence and the geometry of the breach channel of a landslide dam. This information has not been fully exploited. In this study, we identified sedimentary evidence formed by an ancient landslide-dammed lake in the Liqiu River, a left-bank tributary of the Yalong River. The 12 exposures that we investigated mainly consist of typical clay or silt varves deposited in deep water and the Bouma sequence deposited by subaqueous turbidity flows, as well as climbing ripples that formed in a near-shore environment. Based on sedimentary analysis, we inferred that the minimal lake volume of this ancient lake was approximately 2.4 × 108 m3, corresponding to a lake level at 3,187 m a.s.l. The maximal lake extent derived from relict dam morphology reveals a lake volume of 3.2 × 108 m3 at the level of 3,200 m a.s.l. An initial drainage that occurred as the lake water overtopped the landslide dam was suggested to explain the small discrepancy in the lake level. The relict lake has remained stable over a long period of time and has accommodated continuous clay varve deposits. Furthermore, the optically stimulated luminescence dating results illustrate that the dammed lake initiated before 7.9 ka BP and persisted until at least 3.9 ka BP. The long-term cumulative coupled effect of tectonic movement and the rapid river incision rate provided favorable conditions for the failure of the Yuting landslide.